Genomic signatures of artificial selection in fecundity of Pacific white shrimp, Penaeus vannamei - Sui, Juan; Luan, Sheng; Cao, Jiawang; Dai, Ping; Meng, Xianhong; Luo, Kun; Chen, Baolong; Tan, Jian; Fu, Qiang; Kong, Jie (Frontiers in Genetics, 2022)
Penaeus vannamei is the most important economic shrimp in the world. Many selective breeding programs are carried out to improve its production and performance traits. Although great differences in reproductive ability of female P. vannamei under artificial breeding conditions have been reported, the genome-wide adaption of the reproductive ability of domesticated female P. vannamei is less investigated. Here, whole-genome analysis was performed with pooled-DNA sequencing of two fecundity separated bulks, high fecundity bulk (HB) and low fecundity bulk (LB). Each bulk contained 30 individuals from three commercial populations. A sequencing depth of > 30 × was achieved for each bulk, leading to identification of 625,181 and 629,748 SNPs in HB and LB, respectively. Fixation index (Fst) combined with π ratio allowed for identification of 145 selective sweep regions, with a sequence length of 14.5 Mb, accounting for 0.59% of the genome. Among the 145 selective sweep regions, a total of 64,046 SNPs were identified, and further verification was performed by genotyping of 50 candidate SNPs on 60 samples from the offspring of the three populations. In further, 121 genes were screened from the sweep regions. GO annotation and KEGG enrichment analyses showed that partial genes were essential for fecundity regulation. This work provides important information for deeply investigating genomic characteristics for long-term selective breeding on the fecundity of female P. vannamei and will also be important for genome-assisted breeding of P. vannamei in the future.